The analysis of SQ3R in reading learning process for mechanical engineering students of Politeknik Harapan Bersama - Syaefani Arif Romadhon; M. Taufik Qurohman; Iin Indrayanti (ETERNAL (English Teaching Journal), 2021)
This research was motivated by low ability in English subject, reading comprehension in particular among students in Mechanical Engineering study program. Politeknik Harapan Bersama. Based on some related studies, SQ3R technique is as one of learning techniques that proved to enhance reading skills. This research was conducted with the assumption that the technique was able to improve reading comprehension. Therefore, the purpose of the current study was to determine the effect of SQ3R technique on students' reading comprehension. The research presented 2 variables namely SQ3R technique (X) and reading comprehension (Y). Pre-Experimental method of One Group Pretest-Posttest Design was implemented with one class of Mechanical Engineering consisting 26 male and 1 female student involved during the study. Data were gained through cloze test and observation sheet. All data were then processed and analyzed quantitatively to determine the effect of the SQ3R technique on the students' ability to comprehend the passage. The results showed that tcount (5.001) was greater than ttable (2.080). Thus, this can be concluded that SQ3R technique has positive effect (54.4%) on the students' reading comprehension.